2022
DOI: 10.1590/s1677-5538.ibju.2022.99.16
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary techniques of da Vinci SP radical prostatectomy: multicentric collaboration and expert opinion

Abstract: Background: The da Vinci SP robot consists of an innovative single port trocar that houses a flexible camera and three biarticulated arms, which minimizes the number of incisions to assess the surgical site, allowing a less invasive procedure. However, due to its recent release in the market, the current literature reporting SP-RARP is still restricted to a few centers. In this scenario, after performing a literature search with all available techniques of SP-RARP, our objective is to report a multicentric opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…However, previous studies have suggested selective suture ligation of the DVC to preserve the rhabdosphincter and underlying neurovascular components, which may improve the recovery of urinary continence ( 17 ). Other studies revealed that Retzius-sparing RALP contributed to postoperative urinary continence ( 19 , 20 ). These findings indicate the importance of reducing the complications of postoperative urinary incontinence by selecting the optimal surgical procedure.…”
Section: Discussionmentioning
confidence: 94%
“…However, previous studies have suggested selective suture ligation of the DVC to preserve the rhabdosphincter and underlying neurovascular components, which may improve the recovery of urinary continence ( 17 ). Other studies revealed that Retzius-sparing RALP contributed to postoperative urinary continence ( 19 , 20 ). These findings indicate the importance of reducing the complications of postoperative urinary incontinence by selecting the optimal surgical procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Since the acquisition of the da Vinci SP by our center, we have described in previous studies our experience and results with this platform in patients undergoing robotic radical prostatectomy. 17,19,21 Although minimally invasive techniques such as robotic surgery decrease perioperative impacts, surgical outcomes depend on several different factors, such as preoperative patient characteristics, age, SHIM score, cancer stage, and comorbidities. 10,13,22,23 In addition, surgical technique and nerve-sparing degree also play an important role along with postoperative management and patient follow-up protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Since the acquisition of the da Vinci SP by our center, we have described in previous studies our experience and results with this platform in patients undergoing robotic radical prostatectomy. 17,19,21 Although minimally invasive techniques such as robotic surgery decrease perioperative impacts, surgical outcomes depend on several different factors, such as preoperative patient characteristics, age, SHIM score, cancer stage, and comorbidities. 10,13,22,23 In addition, surgical technique and nerve-sparing degree also play an important role along with postoperative management and patient follow-up protocols.…”
Section: Discussionmentioning
confidence: 99%
“…We also used transperitoneal access with an anterior approach, as described by previous studies performed at our institution. 3,[15][16][17][18][19][20][21] None of the groups had abdominal drains placed after the procedure.…”
Section: Da Vinci Sp Surgical Techniquementioning
confidence: 99%